EXPLORING THE INTERCONNECTEDNESS OF COSMOLOGICAL PARAMETERS AND OBSERVATIONS: INSIGHTS INTO THE PROPERTIES AND EVOLUTION OF THE UNIVERSE - Nasution, Budiman; Siagian, Ruben Cornelius; Nurahman, Arip; Alfaris, Lulut (Program Studi Fisika Universitas Negeri Jakarta, 2023)
This research aims to investigate the relationship between Confidence Interval, Hubble Parameter, Comoving Distance, and Distance-Volume Relationship, which are important equations in cosmology. The Confidence Interval equation is used to estimate the range of values for the difference between the mean redshift and Hubble parameter. The Hubble Parameter equation is used to measure the expansion rate of the universe, while the Comoving Distance equation is used to calculate the distance between two objects in the expanding universe, and the Distance-Volume Relationship equation is used to calculate the distance between an observer and a cosmic object based on the object's redshift. This study seeks to address several research questions, including the accuracy of estimating parameters using these equations and the potential for developing more precise equations. The study employs cosmological data analysis using the R program to analyze existing data and gain a better understanding of cosmological parameters. The results of this research contribute to our understanding of the nature and evolution of the universe, providing insights into the distribution of matter and the role of dark matter and dark energy in shaping the universe's evolution. By examining the relationship between cosmological parameters, this study enables us to make predictions about cosmic phenomena and improve the accuracy of future measurements. The findings of this research have implications for cosmological research and can aid in the development of more accurate models and theories in the field of cosmology. Overall, this study provides valuable insights into the fundamental equations in cosmology and their relationships, advancing our understanding of the universe's dynamics and evolution.